Odpowiedzi

2009-11-26T11:06:51+01:00
(2a+y)(2a-y) = 4a² + 2ay + 2ay - y² = 4a² + 4ay - y²

(y+2)(3-y)+(2-3y)² = 3y - y² + 5 - 2y + 4 -3y² = 3y - 4y² + 9




1 5 1
2009-11-26T11:07:53+01:00
A) (3x-y)²=9x²-6xy+y²
b) (2a+y)(2a-y)=4a²-y²
c) (y+2)(3-y)+(2-3y)²=3y-y²+6-2y+4-12y+9y²=8y²-11y+10
d) 3√5(2-√5)-(3-2√5)=6√5-15-3+2√5=8√5-18
2 4 2
Najlepsza Odpowiedź!
2009-11-26T11:08:15+01:00
A) (3x-y)² = (3x-y)(3x -y) = 9x² - 3xy - 3xy + y² = 9x² - 6xy + y²
b) (2a+y)(2a-y)= 4a² - 2ay + 2ay - y² = 4a² -y²
c) (y+2)(3-y)+(2-3y)²= 3y - y² + 6 - 2y + (2 - 3y)(2 - 3y) = y - y² + 6 + 4 - 12y + 9y² = 8y² - 11y + 10

d)3√5(2-√5)-(3-2√5) = 6√5 - 15 - 3 + 2√5 = 8√5 - 18
1 5 1